High-throughput computing for screening the potential alloying elements of a 7xxx aluminum alloy for increasing the alloy resistance to stress corrosion cracking. (1st May 2021) - Ji, Yucheng; Dong, Chaofang; Chen, Leng; Xiao, Kui; Li, Xiaogang
Graphical abstract: Highlights: The type of GBs affects the diffusion of Mg and Zn atoms. Under flow stress and heating, the precipitation rate of η/η' phase at the GBs is accelerated. The distribution of η/η' phase lead to obvious differences in alloys strength and dislocation density. A high-throughput algorithm screened potential 7xxx Al alloying elements that could lower SCC sensitivity. Abstract: In this study, a high-throughput calculation algorithm was compiled for screening the potential alloying elements that can increase the resistance of Al alloy to stress corrosion cracking (SCC). Studies show that the precipitation rate of η/η' phase at the GBs increased by 53 times due to hot rolling. The η/η' phase distribution at GBs decreased the dislocation density by an order of magnitude, which makes the GBs sensitive to SCC. To compensate for these weak sites, the algorithm was utilized to determine the stabilities, diffusion energy barriers, and GB cohesive energy of all elements in the Al.